(untitled) (Journal of Philosophy Culture and Political Science, 2018)
This paper addresses the issue of globalization in Kazakhstan. Modern world culture and globalization is a complex process all aspects of society. The new century and a new world characterized by globalization to humanity is a new problem for the solution of which needs new values and new concept. The concept of globalization is not used by only scientists, but also politicians, journalists, writers in their daily lives. Therefore, this process goes beyond the scientific concepts and demands proof and systematization. Globalization covers all spheres of social life: economy, politics, social relations, culture, and ideology and others surrounding the phenomenon that is the key to the further development and prosperity of Kazakhstan. In the process of globalization, increased competition in politics, economics and international relations. Strongly evolving information and technology. Therefore, at the present stage is especially appreciated focus on creating a culture system for the implementation of globalization. Key words: globalization, a new world, the value of the stability agreement, tranquility, peace, development, technology, culture, cultural relations.